Late-stage functionalization with strain-release warheads enables tunable covalent inhibition - Zachary P. Shultz; Ansar Lee-Sam; Yun-Pu Chang; Luxin Sun; Dylan Grassie; Alessio Gabellini; Kyle Pedretty; Thomas Scattolin; Victoria Izumi; Bin Fang; Samer Sansil; Ramu Kakumanu; et al. (Science, 2026)
Covalent inhibition continues to gain momentum as a strategy for selective protein modulation in both therapeutic and chemical biology contexts. Covalent reactive groups (CRGs) typically engage nucleophilic residues such as cysteine, resulting in targeted protein inactivation. However, common electrophiles such as acrylamides often suffer from nonselective reactivity, leading to off-target effects and toxicity. To overcome these limitations, we developed a modular sulfur(IV) reagent platform for the mild, late-stage installation of sulfonyl- and sulfonimidoyl-bicyclobutane motifs with complete cysteine selectivity. This methodology enables access to diverse sulfur(VI) CRGs with tunable strain-release reactivity. Incorporation into US Food and Drug Administration–approved covalent inhibitors demonstrated effective bioisosteric replacement of acrylamides and the potential of strain-release CRGs for selective protein targeting. Preclinical studies in mice have validated this approach, highlighting its promise for next-generation covalent drug design.